Investigation of closed compartment moulding for pull-winding process - Malek Ya’acob, Abdul; Daniel Aizat Mohd Razali, Mohamad; Abdillah Anwar, Umar; Arif Hakimi Mohd Radhi, Mohd; Aizat Afifi Ishak, Muhammad; Minhat, Mulia; Dahri Mohd Aris, Khairul; Khudri Johari, Muhd; Teh, Casey (International Journal of Engineering and Technology, 2018)
This project investigates the closed compartment moulding design for pull-winding process. This is a continuation of an initial study that involved discovering how the permeability effect inside a close compartment in pull-winding processing. The mould has been designed to ensure resin penetration to the preform. The mould design has been divided into three parts for easy installation, maintenance and also cleaning after use. The mould has been tested on an actual production line at TenAsia Sdn. Bhd. The test is conducted by pulling mechanism where the machine pulls the preform winding forward when it is switched on. In this process, the resin is flowing through the hose and it has been sprayed out by the nozzle inside the mould to the preform. The test has been done using 2, 4 and 6 nozzles with various pressures to determine which one is the most suitable for penetration and covering up the preform. Based on the results, the most economical and productive design has been identified as spray type with 2 upper and lower nozzles running at an appropriate pressure of 20 psi. This pressure has been chosen based on the area covered on the preform surfaces and time taken to penetrate the preform layer. In conclusion, 20 psi pressure works better due to the resinâ€™s deeper penetration in shorter time, less mist and very minimal excess resin.Â Â